Polymer-Modified Hydraulic-Cement Mixtures 1993
DOI: 10.1520/stp25548s
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Polymer-Modified Mortars Using Epoxy Resin Without Hardener

Abstract: In the preparation of conventional polymer-modified mortars using epoxy resin, the use of any hardener has been considered indispensable for the hardening of the epoxy resin. The authors have noticed that the hardening of epoxy resin occurs in the presence of alkalis in cement mortar. Polymer-modified mortars using epoxy resin without any hardener are prepared with various polymer-cement ratios, and tested for strength, adhesion, water absorption, drying shrinkage, chloride ion penetration and carbonation. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…They are also used as an admixture in concrete to impart certain effects on mortars. However, the preparation of conventional polymer-modified mortars using epoxy resins cannot be realized without the use of hardener [1]. A previous study by Kakiuch [2] showed that epoxy resins can harden in the presence of alkalis whereby the authors succeeded in developing polymer-modified mortars using epoxy resin without any hardener.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also used as an admixture in concrete to impart certain effects on mortars. However, the preparation of conventional polymer-modified mortars using epoxy resins cannot be realized without the use of hardener [1]. A previous study by Kakiuch [2] showed that epoxy resins can harden in the presence of alkalis whereby the authors succeeded in developing polymer-modified mortars using epoxy resin without any hardener.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study by Kakiuch [2] showed that epoxy resins can harden in the presence of alkalis whereby the authors succeeded in developing polymer-modified mortars using epoxy resin without any hardener. The aforementioned application was countered by Ohama [3] who posited that epoxy resin without hardener, in concrete and mortar at ambient temperature has lower rate of hardening and strength. In order to overcome that problem, an autoclave curing and steam curing process was used to bring about early strength development of epoxy-modified mortar and concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Ohama and his co-workers have first proposed and demonstrated that this process can proceed inside the cement paste [22], allowing for some specific features of epoxy-cement composites, like ability to partial self-repairing [23].…”
Section: Epoxy-cement Mortars With and Without Hardenermentioning
confidence: 99%
“…The higher pore volume compared to the unmodified mortar could also have increased either the volume of voids available to accommodate ASR expanding products or the leaching of alkalis away from the PCM specimens in the humid conditions, thus contributing to the observed reduced expansion. Epoxy-modified mortars have also been reported to have self-healing properties [35], which may contribute to an increased resistance to crack opening and thus to reduce expansion.…”
Section: Previous Studies On Asr In Pcmsmentioning
confidence: 99%